СРАВНИТЕЛЬНОЕ ИЗУЧЕНИЕ АНГЛИЙСКИХ, УЗБЕКСКИХ И КАРАКАЛПАКСКИХ ПРОВЕРБИАЛЬНЫХ ОБРАЗОВАНИЙ В ТЕКСТАХ ХУДОЖЕСТВЕННОЙ ЛИТЕРАТУРЫ - Жалгасов, Н.М. (SCIENCE and SOCIETY, 2024)
This article deals with the study of the specifics of English, Uzbek and Karakalpak proverbial formations in literary texts. This article analyzes the features of the use of proverbial formations of the compared languages in literary texts. The theoretical content of the article is proven by examples of proverbs of the compared languages.